Pilus–encoding islets in S. agalactiae and its association with antibacterial resistance and serotype distribution. (March 2018) - Khodaei, Farzaneh; Najafi, Mohammad; Hasani, Alka; Kalantar, Enayatollah; Sharifi, Esmail; Amini, Abbas; Aghazadeh, Mohammad
Abstract: Group B Streptococcus (GBS) is a versatile organism which uses multiple virulence factors which bind to the surface of epithelial cells. Pili are one of virulence factors detected in recent years. A total of 90 isolates were collected from invasive and non-invasive isolates among adults throughout 2014-2015. Isolates were serotyped at molecular level based on capsular polysaccharide ( cps ) serotyping and analyzed for pilus island profiles, scp B gene, and hvgA gene presence. Isolates were subjected to antimicrobial susceptibility towards penicillin, tetracycline, erythromycin, clindamycin, moxifloxacin, levofloxacin, and vancomycin by disk diffusion method and MICs for erythromycin and clindamycin were determined by broth dilution methods. Overall, 4 serotypes were identified, serotype III (68.88%), V (20%), II (10%) and Ib (1.11%) and hvgA gene was detected in 7.7% (n = 7) of the isolates; all were serotype III/ST 17. All isolates were susceptible to penicillin and vancomycin, except one isolate which showed intermediate resistance to penicillin and other complete resistance to vancomycin. Isolates were resistant to tetracycline (98%), erythromycin (25%), clindamycin (22%), moxifloxacin (8%), and levofloxacin (6%). The scp B gene was detected in all isolates, while isolates harbored at least one PI, of which the PI-1+PI-2a was the most frequent combination observed. Our data show the presence of the relation between serotype or pilus genes among clinical isolates of Streptococcus agalactiae . These data are principal to help in designing prevention and treatment strategies for GBS infections in the region.